Flow simulation study on bed bath for bedridden patient - Azmi, Nur Fatihah; Ismail, Muhammad Hazim; Mokhtar, Nur Hazwani; Ramli, Mizah; Saleman, Abdul Rafeq (Semarak Ilmu Publishing, 2023)
Easy tasks such as showering or bathing independently are impossible for a bedridden individual. This paper presents a comprehensive study on designing an easy shower specifically tailored for bedridden patients. The challenges bedridden individuals face in maintaining personal hygiene are highlighted, emphasizing the importance of a suitable bathing system to enhance their quality of life. The proposed design aims to address these challenges and improve caregiving efficiency. The chosen methodology involves a weighted decision matrix to select the optimal design, followed by flow simulation using SolidWorks Flow Simulation software to evaluate its performance. The paper's objectives include designing an efficient easy shower model, assessing its performance via simulation, and analyzing the impact of various velocity settings on its functionality. Three design concepts were proposed, with Design A selected as the optimal choice due to its lightweight, high water capacity, ease of handling, and low production cost. Modifications were made to enhance its water pressure efficiency. The simulation encompassed different velocity settings, with flow trajectories analyzed within the tank and at the water outlet. These boundary conditions included analysis type (internal), fluids (water), default wall thermal condition (adiabatic wall), pressure (101325 Pa), temperature (293.2 K), and velocity in the Y direction (5 m/s for water inlet and 0.5 m/s for water outlet). In the first simulation, all the results obtained were within the specified velocity range of 0.5 m/s, 2 m/s, and 5 m/s. The analysis of flow trajectories revealed distinct flow patterns and velocities for different velocity values, indicating stable and controlled environments within the tank and efficient water discharge through the outlet in Design A. However, errors were observed in the water outlet simulation due to the presence of vortices, which impacted the results. Recommendations were made to address these challenges, such as modifying the design to eliminate or minimize vortex effects. In conclusion, this study contributes to the well-being of bedridden patients by proposing an improved bathing mechanism, enhancing caregiving efficiency, and offering insights into design optimization and simulation challenges. The proposed design could have a significant positive impact on the lives of bedridden patients and caregivers.